2015
DOI: 10.1111/liv.13009
|View full text |Cite
|
Sign up to set email alerts
|

The enteric microbiome in hepatobiliary health and disease

Abstract: Increasing evidence points to the contribution of the intestinal microbiome as a potentially key determinant in the initiation and/or progression of hepatobiliary disease. While current understanding of this dynamic is incomplete, exciting insights are continually being made and more are expected given the developments in molecular and high-throughput omics techniques. In this brief review, we provide a practical and updated synopsis of the interaction of the intestinal microbiome with the liver and its downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 68 publications
0
25
0
1
Order By: Relevance
“…Gut-derived bacterial products, such as LPS, activate the inflammatory cascade in immune cells, modulate the function of liver parenchymal cells, and contribute to chronic liver diseases [171,172]. Recently, it was showed that the expression of NLR pyrin domain-containing protein 3 (Nlrp3) inflammasome is increased in reactive cholangiocytes of both in vitro and in vivo models of a PSC, leading to the secretion of IL-18 and alteration of the epithelial barrier function of cholangiocytes with significantly decreased the expression of zonulin-1 and e-cadherin [173].…”
Section: The Reactive Cholangiocytementioning
confidence: 99%
“…Gut-derived bacterial products, such as LPS, activate the inflammatory cascade in immune cells, modulate the function of liver parenchymal cells, and contribute to chronic liver diseases [171,172]. Recently, it was showed that the expression of NLR pyrin domain-containing protein 3 (Nlrp3) inflammasome is increased in reactive cholangiocytes of both in vitro and in vivo models of a PSC, leading to the secretion of IL-18 and alteration of the epithelial barrier function of cholangiocytes with significantly decreased the expression of zonulin-1 and e-cadherin [173].…”
Section: The Reactive Cholangiocytementioning
confidence: 99%
“…Гепатит С залишається однією з провідних проблем внутрішньолікарняних інфекцій, пов'язаних із гемо-трансфузіями, введенням препаратів крові, медичними інвазивними маніпуляціями з діагностичною та ліку-вальною метою [1,2]. Більше ніж 2 % населення світу заражено цим вірусом.…”
Section: вступunclassified
“…PRRs, which include toll-like receptors (TLRs) and nucleotide-binding oligomerization domain receptors (NLRs), (35) are plasma membrane and/or intracytoplasmic proteins that sense and respond to pathogen-associated molecular patterns (PAMPs) such as microbial lipid, protein and nucleic acid moieties (6) as well as microbial metabolites (eg bile acids, (7) short-chain fatty acids, (8) and phosphatidylcholine. (7, 9) …”
Section: Microbial Recognition: the Host Innate Immune Systemmentioning
confidence: 99%
“…This induces signal transduction cascades which involve recruitment of adaptor proteins and activation of a multitude of downstream signaling molecules, thus culminating in: i) nuclear translocation of transcription factors, ii) biosynthesis of interleukins, interferons, and/or chemokines, eg tumor necrosis factor (TNF-α) and interleukin (IL-1β), and iii) regional and recruited cell responses, including those of the adaptive immune system (Figure 1). (5) NLRs function similarly to and often in conjunction with TLRs.…”
Section: Microbial Recognition: the Host Innate Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation